Hazardous waste management - LaGrega, Michael D.; Buckingham, Phillip L.; Evans, Jeffrey C. (McGraw-Hill series in water resources and environmental engineering, 2001)
Provides a useful introduction to hazardous waste management, with information on methods of treatment, disposal, and site remediation. This book discusses the changes in the field, such as changes in emphasis from site assessments to site remediation, from new facility siting to pollution prevention, and from a emerging market to a mature market.